Financial performance difference analysis of Mandiri Islamic Bank by using sharia value added and income statement approach on 2007-2011 period - Octa Eka Prasetya (STIE Perbanas Surabaya, 2013)
This study tries to analyze the difference of financial performance of Islamic banks byusing income statement approach and value added approach based on financial ratio.The financial ratio which is used consists of ROA, ROE, and the ratio between thetotal net income by earning assets, NPM, and BOPO. The data for analysis weretaken from PT. Bank Syariah Mandiri Indonesia. Thus, the population of this researchis the financial report of PT. Bank Syariah Mandiri; while the sample of this researchwas the financial report year 2007- 2009 for each approaches that are Income StatementApproach and Value Added Approach. The means of analysis to prove the hypothesisof this research is an independent sample t-test. It shows that the averagefinancial ratio (ROA, ROE, net profit ratio of productive assets, and NPM). There aresignificant differences between the Income Statement Approach and Value AddedApproach, while the BOPO ratio between the Income Statement Approach and ValueAdded Approach has no difference. Yet, when viewed in the overall level of profitability,it shows that there are significant differences between the Income Statement Approachand Value Added Approach.